Uncertainty in low back pain care – insights from an ethnographic study. Issue 5 (27th February 2023) - Costa, N.; Olson, R.; Mescouto, K.; Hodges, P. W.; Dillon, M.; Evans, K.; Walsh, K.; Jensen, N.; Setchell, J.
Abstract: Purpose: To explore how uncertainty plays out in low back pain (LBP) care and investigate how clinicians manage accompanying emotions/tensions. Materials and methods: We conducted ethnographic observations of clinical encounters in a private physiotherapy practice and a public multidisciplinary pain clinic. Our qualitative reflexive thematic analysis involved abductive thematic principles informed by Fox and Katz (medical uncertainty) and Ahmed (emotions). Results: We identified three themes. (1) Sources of uncertainty: both patients and clinicians expressed uncertainty during clinical encounters (e.g., causes of LBP, mismatch between imaging findings and presentation). Such uncertainty was often accompanied by emotions – anger, tiredness, frustration. (2) Neglecting complexity: clinicians often attempted to decrease uncertainty and associated emotions by providing narrow answers to questions about LBP. At times, clinicians' denial of uncertainty also appeared to deny patients the right to make informed decisions about treatments. (3) Attending to uncertainty?: clinicians attended to uncertainty through logical reasoning, reassurance, acknowledgement, personalising care, shifting power, adjusting language and disclosing risks. Conclusions: Uncertainty pervades LBP care and is often accompanied by emotions, emphasising the need for a healthcare culture that recognises the emotional dimensions of patient-clinician interactions and prepares clinicians and patients to be more accepting of, and clearly communicate about, uncertainty. IMPLICATIONS FOR REHABILITATION: Uncertainty pervades LBP care and is often accompanied by emotions. Neglecting complexity in LBP care may compromise person-centred care. Acknowledging uncertainty can enhance communication, balance patient-clinician relationships and address human aspects of care.